Communication breakdown: how conflict can promote responsible leadership in students. Issue 1 (1st January 2016) - Higham, Rupert
ABSTRACT: This study of an outdoor-based leadership course for teenagers shows how open-ended, difficult group tasks can enable participants to develop 'dispositions for learning', which promote 'responsible leadership'. The latter is defined as responding ethically and uniquely to encounters with difference. Uses of educational psychology often circumscribe 'challenge' to avoid risk and promote predictability; a riskier, wilder conception is proposed instead through a 'pedagogy of challenge'. It is shown that course participants reflected on their most difficult moments, most of which ended in failure and dispute, as their most powerful and memorable learning experiences. Implications for schools and classrooms are considered.